Wasted myocardial work may affect left ventricular remodelling occurrence after primary percutaneous coronary revascularization. (4th February 2022) - Caminiti, R; Vetta, G; Parlavecchio, A; Pelaggi, G; Lofrumento, F; Licordari, R; Cusma, M; Manganaro, R; Pucci, M; Radano, I; Citro, R; Carerj, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Left ventricular function recovery (LV-REC) or left ventricular adverse remodelling (LV-REM) after acute myocardial infarction (AMI) play an important role for identifying patients at risk of heart failure. Purpose: In this study we aim to evaluate the usefulness of non-invasive myocardial work (MW), a new index of global and regional myocardial performance, to predict LV-REC or LV-REM after AMI. Methods: Fifty patients with AMI (mean age, 63, 8 ±13, 4 years), treated by primary percutaneous coronary intervention (PCI), were prospectively enrolled. They underwent a baseline transthoracic Doppler echocardiography (TTE) within 48 hours after PCI and a second TTE after a median of 31 days during the follow-up. MW was derived from the strain-pressure loops, integrating in its calculation the non-invasive arterial pressure, according to standard speckle tracking echocardiography recommendations. LV-REC was defined as an absolute improvement of left ventricular ejection fraction (LVEF) ≥ 5% from LVEF at baseline, whereas LV-REM was defined as an increase of ≥ 20% of the LV end diastolic volume (LVEDV) at 1 month follow up. Results: We overall found a significant improvement from baseline to one-month follow-up for values of LVEF (49, 8 ± 9, 5 % vs 52, 8 ± 9, 3 %, p = 0.001), Global Longitudinal Strain (GLS) (-13, 4 ± 3, 9 % vs -18, 7 ± 5, 4 %, p = 0.016), Global Work Index (GWI) (1368, 6 ±435, 2 vs 1788 ±493 mmHg/%, p = 0.0001), Global Work Efficiency (GWE) (89, 96 ± 9, 3 % vs 91, 3 ± 6, 4 %, p = 0.001), Global Constructive Work (GCW) (1619, 16 ± 497, 9 mmHg/% vs 2008, 6 ± 535, 3 mmHg/%, p = 0.0001), Global Wasted Work (GWW) (188, 8 ± 19, 8 mmHg/% vs 149, 2 ± 16, 5 mmHg/%). However, LV-REC at 1 month of follow-up was observed only in 36 % of the population enrolled, whereas LV-REM was described in 18% of cases. Using ROC curve analysis, we identified a cut off value of 202 mmHg/% for baseline GWW (Sensitivity 75%, Specificity 62%, AUC 0.6667, CI 95%: 0, 51618 - 0, 81715, p =0.0001) to identify patients with LV-REM at 1 month. With regards to conventional echo parameters, patients with LV-REC showed lower baseline Wall Motion Score Index (WMSI) than those without LV-REC (1, 73 vs 1, 38, p = 0.007). Conclusions: Among standard and advanced TTE parameters, only baseline GWW is able to predict early LV-REM at 1 month after primary PCI. Therefore, it could be used during baseline evaluation of AMI patients for a more accurate stratification of those at higher risk of heart failure. However, further larger scale studies are needed to validate these findings.